2021
DOI: 10.1021/acs.jpca.1c03433
|View full text |Cite
|
Sign up to set email alerts
|

Multibounce and Subsurface Scattering of H Atoms Colliding with a van der Waals Solid

Abstract: We report the results of inelastic differential scattering experiments and full-dimensional molecular dynamics trajectory simulations for 2.76 eV H atoms colliding at a surface of solid xenon. The interaction potential is based on an effective medium theory (EMT) fit to density functional theory (DFT) energies. The translational energy-loss distributions derived from experiment and theory are in excellent agreement. By analyzing trajectories, we find that only a minority of the scattering results from simple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Because the experiment can only detect the final energy of the scattered particles, we now analyze the role of surface penetration which has recently been identified to result in higher energy losses. , The upper panels of Figure show contour plots which provide the number of specular scattering events as a function of energy loss and depth of penetration. A clear correlation between the energy loss and the depth of penetration can be inferred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the experiment can only detect the final energy of the scattered particles, we now analyze the role of surface penetration which has recently been identified to result in higher energy losses. , The upper panels of Figure show contour plots which provide the number of specular scattering events as a function of energy loss and depth of penetration. A clear correlation between the energy loss and the depth of penetration can be inferred.…”
Section: Resultsmentioning
confidence: 99%
“…A series of scattering experiments have been performed in which high-energy H atoms were shot onto fcc(111) metal surfaces. In combination with electronically nonadiabatic molecular dynamics (MD) simulations, it was demonstrated that the energy transfer from the projectile to the metallic surface is dominated by electronic excitations. When the metal surface is exchanged with a noble-gas surface, however, the excess energy is completely taken up by the lattice, and surface penetration was identified to be the first step in adsorption . Regardless of the recent advance on H atom scattering studies, the role of the surface structure has not been the subject of investigation yet.…”
Section: Introductionmentioning
confidence: 99%
“…The Effective Medium Theory (EMT) has proven useful to describe gas-surface interactions for fcc metals. 2,14,[22][23][24][26][27][28][29][30] Here, we extend the previously formulated EMT formalism to the case of bcc metals.…”
Section: Effective Medium Theorymentioning
confidence: 99%
“…We emphasize that neglecting the random force, as has sometimes been done, 44 can lead to spurious results. 14 The EMT-PES and the Langevin propagator integrating eqn (30) are implemented in our homemade program md_tian2 available at a public repository. 45 The MD trajectories simulating H scattering from a metal surface were started with a H atom placed at 6 Å above the surface with a lateral position chosen randomly.…”
Section: Non-adiabatic Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The first, effective medium theory (EMT) 29,30 is a full dimensional PES approach previously used for H atom scattering from fcc(111) surfaces. 3,4,31 It models excitation of phonons by full dimensional classical MD and the frictional force is computed from EMT-background electron densities associated with the moving lattice. The second is a corrugation reduction procedure (CRP), [32][33][34] which has also been applied to H atom scattering from metal surfaces 7 as well as hydrogen recombination.…”
Section: Introductionmentioning
confidence: 99%